Douro cruises experiences: The mediating role of co-creation in revisit intention - Gondar, Bianca Veiga (2023)
Consumers are increasingly demanding in their choices. In line with the competitive nature of the tourism, companies must adopt procedures and policies that enable them to understand consumers' needs in order to provide them with a service that meets their requirements. This study aims to understand the impact of co-creation on revisit intention in tourism services, especially on the Douro cruises. In this sense, we seek to understand which variables of the cruise experience influence not only the cruisers intention to revisit but also their co-creation experience and how the last one may influence the intention to return as well. In the scope of the study, questionnaires were carried out, applied at the end of the excursions that tourists made, having as departure and arrival point the Gaia pier. A sample of 264 visitors was surveyed between April and June 2023. The study demonstrates the influence of the four components of the cruise experience on co-creation and revisit intention as well as how co-creation assumes a mediating role. However, the study showed that only two of the variables influence co-creation and this one adopts a mediator role in the relationship between the experience economy model and revisit intention. The latter is only influenced by one variable of the model. This research contributes to the topic of co-creation and revisit intention in the cruise sector in Douro region, in which it is a recent topic in the literature, as well as having a significant contribution to the application in business strategies.